2017
DOI: 10.1002/oby.22001
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Metabolic Profiles are Associated with Colorectal Adenomas and Serrated Polyps

Abstract: Objective: Prevention of colorectal cancer (CRC) by colonoscopy is recommended according to age and personal/familial history. Metabolic alterations are associated with colorectal adenomas, but data are scarce regarding serrated polyps and advanced polyps. The aim of this study was to evaluate the association between metabolic alterations and colorectal polyp type and advanced polyps. Methods: A case-control study was conducted among consecutive subjects, 40 to 70 years old, who underwent screening/diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…A cohort study involving 2244 patients indicated that visceral adipose tissue was dose-dependently associated with colorectal adenoma [23]. Similarly, abdominal obesity, hypertension, and a high HbA1c% increase the risk for polyps [24]. Consistent with previous reports, we found that uric acid and MS index were also strongly associated with colon polyp.…”
Section: Discussionsupporting
confidence: 90%
“…A cohort study involving 2244 patients indicated that visceral adipose tissue was dose-dependently associated with colorectal adenoma [23]. Similarly, abdominal obesity, hypertension, and a high HbA1c% increase the risk for polyps [24]. Consistent with previous reports, we found that uric acid and MS index were also strongly associated with colon polyp.…”
Section: Discussionsupporting
confidence: 90%
“…Monosodium urate crystals stimulate inflammatory response by activation of toll-like receptor 4, which strongly promotes leukocyte to produce proinflammatory factors, which play a critical role in regulating neoplasm formation and cancer progression [12]. In other studies, abdominal obesity and hypertension were correlated with adenoma type polyps, whereas the strongest predictor for serrated polyps was a high triglyceride (TG) to high-density lipoprotein cholesterol levels (TG/HDL) ratio [13]. In obese patients, adipose tissue releases free fatty acids, growth factors, adipokines, and other proinflammatory factors, known to play a key role in regulating malignant transformation and cancer progression [14].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated HbA1c levels, abdominal obesity and hypertension correlate with the risk to develop gastrointestinal polyps. In addition, improper lipid metabolism with a high triglyceride to HDL ratio has been found to increase the risk to develop serrated adenomas [271].…”
Section: Lipidsmentioning
confidence: 99%